2020
DOI: 10.1016/j.scitotenv.2020.140243
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular tracks and the influence of land use and habitat protection in the British uplands

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…and unsurfaced road networks in the UK uplands alone, with some 6,000 km identified (Clutterbuck, Burton, et al, 2020), is some cause for concern in the light of findings highlighted by our study. Our experimental site is well-vegetated and in relatively healthy condition adjacent to the track.…”
Section: Additional Considerationsmentioning
confidence: 74%
See 1 more Smart Citation
“…and unsurfaced road networks in the UK uplands alone, with some 6,000 km identified (Clutterbuck, Burton, et al, 2020), is some cause for concern in the light of findings highlighted by our study. Our experimental site is well-vegetated and in relatively healthy condition adjacent to the track.…”
Section: Additional Considerationsmentioning
confidence: 74%
“…There has been a rapid expansion of both surfaced and unsurfaced track networks for resource access and leisure purposes, in what are nominally protected blanket bog areas in the UK, with a mean track density of 1.76 ± 0.10 km km −2 across peatland sites (Clutterbuck, Burton, et al, 2020) with greater densities associated with vegetation management for gun‐sports.. Despite rapid growth of these peatland track networks, there are significant gaps in knowledge about the environmental impacts of tracks.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the density of tracks across the UK found that, in an example 6855 km 2 of blanket peatland survey area, there was around 5700 km of vehicular track, with large lengths in 'protected areas' (Clutterbuck et al, 2020). Many of these tracks were mapped in areas where land management for the purpose of game shooting often takes place.…”
Section: Roads Within Peatlandsmentioning
confidence: 99%
“…Many of these tracks were mapped in areas where land management for the purpose of game shooting often takes place. The prevalence of these sizable track and road networks in nominally protected areas suggests the need for more robust data-driven regulation of consent to construct tracks (Clutterbuck et al, 2020). In some countries there may be little regulation for infrastructure and very limited studies on impacts, meaning that roads may be built with little or no consideration given to the potentially detrimental effects of such construction (Alamgir et al, 2019;Lilleskov et al, 2019).…”
Section: Roads Within Peatlandsmentioning
confidence: 99%
See 1 more Smart Citation